PEMANFAATAN BULLETIN BOARD PADA WEBSITE FRISCO PUBLIC LIBRARY - Sudiar, Nining (Jurnal Ilmu Budaya, 2013)
The development of infomation technology today is the need of institution or organizahon. This development also affects library. One of the usages of information technology used in library is to support communications by library-website. Website can provide more· information such as multimedia· .service, e-mail, promotion site and interactive communication. Frisco public libra,y is a public library established by Frisco society and bulletin baard in Frisco S website functions to deliver messeges. Fiturs used are (1) MLK multimedia exhibit (2) Upcoming event, (3) Read to over, (4) Homework Help and (5) e-mail tutorial. The-bulletin board of Frisco :S public library is interesting because it has becautiful choice of color, appropriate choice of pictures which are related to the theme and detail and informative information, i-life concept which makes it easy for the users to access information anytime, anywhere.